Seismic performance of steel-PEC spliced frame beam. (October 2022) - Yao, Yifan; Huang, Hua; Zhang, Wei; Ye, Yanxia; Xin, Li; Liu, Yuan
Abstract: In this paper we propose a novel form known as the steel-PEC spliced frame beam (SPSFB), which is intended to maintain the advantages of the PEC beam while reducing the consumption of steel. In the SPSFB, an independent H-beam (mid-portion beam) is replaced by the PEC beam with a thinner flange. The PEC and stub beams are connected by web bolts, a welded flange, and a girth welded flange cover plate to improve flexural capacity. Low cycle loading tests were conducted on five SPSFB specimens testing the variables of the concrete strength, the length of the stub beam, and the length of flange-plates. Two failure modes were observed, and the related seismic behavior was investigated. When the damage occurred at the bottom of the PEC beam, higher grade concrete was correlated with better seismic performance. When the damage occurred at the bottom of the stub beam, setting an appropriate length of stub beam and flange-plate can improve the hysteretic capacity and further reduce steel consumption. Based on elastic and plastic analysis, the bearing capacities and deformation were calculated. The calculated results agreed well with the experimental results. Highlights: A hollow-core partially-encased composite beams are investigated experimentally. The shear capacity under static loading is studied and the failure mechanism was analyzed as well. Modified Deformation Coordination Truss-arch model is proposed.